Persistent Response to a Combination Treatment Featuring a Targeted Agent and an Immune Checkpoint Inhibitor in a Patient With Collecting Duct Renal Carcinoma: A Case Report and Literature Review - Zhou, Weimin; Huang, Ji; He, Qiuming; Luo, Qingfeng; Zhang, Xiaofang; Tao, Xuewei; Dong, Hanzhi; Tu, Xinhua (Frontiers in Oncology, 2021)
Collecting duct carcinoma (CDC) is a rare and highly aggressive subtype of kidney cancer that is associated with a poor prognosis. At present, there is no effective treatment for CDC. Herein, we report a case of metastatic CDC treated with a combination of a tyrosine kinase inhibitor and an immune checkpoint inhibitor. A 67-year-old male was diagnosed with CDC with lung and bone metastasis. Pazopanib and camrelizumab were administered after cytoreductive nephrectomy. The patient achieved a partial response after one cycle of treatment; however, he then experienced serious drug-induced hepatic injury. Therefore, we discontinued camrelizumab and administered monotherapy with pazopanib. Three months later, the cancer had progressed and axitinib and sintilimab were administered. The patient achieved a partial response, accompanied by the complete disappearance of the metastatic lesion in the lung. The patient had an excellent physical status after 11 months. This is the first reported case of metastatic CDC successfully treated with a combination of a tyrosine kinase inhibitor and an immune checkpoint inhibitor. This form of combination treatment may be an effective option for treating metastatic CDC.